Value of a football club in the context of social media - Chynał, Piotr; Cieśliński, Wojciech B.; Perechuda, Igor (Business Informatics, 2014)
The paper presents an approach to the valuation of specific sports businesses – commercial football clubs in the context of social media factors. The authors show specific value definitions from philosophical to financial approaches. Research shows us that to understand and measure the value of football clubs is not as simple as in non-sports companies. The problem lies inside of intangible assets that from an accounting viewpoint do not constitute all the factors which build the value of the club. One of those factors is social media and their influence on football business
Informatyka Ekonomiczna = Business Informatics, 2014, Nr 4 (34), s. 47-57
Keywords: value; economic value; football clubs; social media; wartość; wartość ekonomiczna; kluby piłkarskie